2017
DOI: 10.1111/aos.13560
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative aqueous humour flare as a surrogate marker for proliferative vitreoretinopathy development

Abstract: Flare values both at 2 and 6 weeks postoperatively seem a good surrogate marker in terms of sensitivity and specificity for the development of postoperative PVR but have only a modest positive predictive value. The 2-week value would be more useful in terms of early recognition of high-risk patients and hence give the possibility to better study effects of treatment methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
1
8
0
2
Order By: Relevance
“…Total protein concentration in the vitreous was investigated in eyes with retinal detachment and higher vitreous protein levels were found in eyes with PVR [29] . Our result is accordance with those reported by Mudler et al [30] showing a significant association between the higher flare values at both 2 and 6wk postoperatively and the development of postoperative PVR in eyes undergoing PPV for RRD. Recently, Narala et al [19] reported a significant association between the preoperative flare of grade ≥2+ and postoperative failure in eyes undergoing vitrectomy for PVR.…”
Section: Resultssupporting
confidence: 94%
“…Total protein concentration in the vitreous was investigated in eyes with retinal detachment and higher vitreous protein levels were found in eyes with PVR [29] . Our result is accordance with those reported by Mudler et al [30] showing a significant association between the higher flare values at both 2 and 6wk postoperatively and the development of postoperative PVR in eyes undergoing PPV for RRD. Recently, Narala et al [19] reported a significant association between the preoperative flare of grade ≥2+ and postoperative failure in eyes undergoing vitrectomy for PVR.…”
Section: Resultssupporting
confidence: 94%
“…Since there seem to be numerous factors influencing LFP, a comprehensive scientific analysis of possible associations is desirable. Few studies have investigated LFP in eyes with RRD [3,4,[10][11][12], and to date no data has been published describing the potential associations between laser flare values, anatomical details, and symptom duration in RRD. We investigated these characteristics to enhance existing knowledge and as experience has shown that they are often associated with each other in everyday clinical practice in the care of patients with retinal detachment.…”
Section: Discussionmentioning
confidence: 99%
“…Yet LFP values seem to have a predictive value regarding the postoperative PVR risk. As a consequence, the value of preoperative laser flare values as a predictor for PVR remains unclear [ 10 , 11 ]. The complex problem of PVR development and the associated rate of retinal re-detachment after primary surgical success is currently the subject of intensive research efforts with the aim to find preventive and therapeutic options.…”
Section: Introductionmentioning
confidence: 99%
“… 30 Furthermore, a connection between aqueous flare levels and the development of postoperative proliferative vitreoretinopathy has been identified. 31 Interestingly, the preoperative aqueous flare values ranged considerably between the cataract surgery patients. Relative changes in aqueous flare compared to the absolute aqueous flare values seemed to better reflect the BAB breakdown induced macular changes postoperatively.…”
Section: Discussionmentioning
confidence: 99%